Comparison of medicinal feed additives on health and growth performance of beef calves grazing native grass pasture - M.P. Epp; B. Greenwood; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2010)
Optimizing growth rate is an important contributor to overall profitability for stocker cattle grazing native Flint Hills pasture. Disease challenges from pinkeye and foot rot have traditionally been problems that compromise health and productivity of stocker cattle in this grazing region. Use of medicinal feed additives as a part of a supplementation program may prevent health problems and improve overall productivity during a spring/summer grazing season.
Keywords: Cattlemen' s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen' s Day; Beef; Health; Growth performance; Growth rate